ANALISIS FAKTOR-FAKTOR TURNOVER INTENTION KARYAWAN DALAM TINJAUAN IKLIM PERUSAHAAN - Darmeinis; Afni Basriani (Pusat Riset dan Inovasi Nasional, 2022)
The phenomenon of employee turnover intention in the company is very likely to occur. The causes of this phenomenon are many and varied. In this study, the various factors that cause turnover intention are discussed, how the relevant factors influence, and solutions to overcome the problem of employee turnover intention based on literature studies and content analysis data analysis techniques. The result is that there are various factors that affect the level of employee turnover intention, each of which has a significant positive and negative influence, so that the solution to the problem also differs from one factor to another.